A Study of Reading Comprehension Ability and Communication and Collaboration Skills of Grade 7th Students Using 4MAT Learning Management - Sopanuson, Thanakorn; Keeratichamroen, Wasana (Ratchaphruek Journal, 2021)
This article was apre-experimental design research and aimed to 1) compare reading comprehension ability of grade 7 students using 4MAT learning management before and after learning management 2) compare reading comprehension ability of grade 7 students using 4MAT learning management after learning management with 70 percent criterion and 3) compare communication and collaboration skills of grade 7 students using 4MAT learning management before and after learning management. The research samples were 17 of grade 7 students at Bangamphan Witthayakhom school, Bumnetnarong district, Chaiyaphum province, in the second academic year of 2020, selected by the Custer Random Sampling. The instruments of this study consisted of 6 leaning lesson plans for 12 hours, reading comprehension ability test and communication and collaboration skills assessment. Data were analyzed by percentage, average, standard deviation, and t-test. The study revealed that 1) reading comprehension ability of grade 7 students using 4MAT learning management after learning management was higher than that before learning management at .05 level of significance 2) reading comprehension ability of grade 7 students using 4MAT learning management after learning management was higher than 70 percent criterion with not statistical significance at .05 level and 3) the post-communication and collaboration skills score of communication and collaboration skills of grade 7 students was significantly higher than pre-communication and collaboration skills score at .05 level of significance.